Poetry Therapy, Disability, and Trauma Expression: A Therapeutic-Phenomenological Perspective - Ahmadi, Anas; Yulianto, Bambang; Khoiri, Abdul Aziz; Yani, Muhammad Turhan; Jamain, Norfaizal Bin; Yusuf, Kamal; Efendi, Agik Nur; Hariyati, Nuria Reny; Savira, Siti Ina; Khozin, Nur (Journal of Intellectual Disability - Diagnosis and Treatment, 2025)
This study aims to explore how individuals with disabilities express traumatic experiences through literary works from a therapeutic-phenomenological perspective. The research employs a qualitative-phenomenological method, with data collected from 45 literary works written by individuals with disabilities. The therapeutic process involved filtering, handling, and follow-up stages, involving 45 participants with disabilities. Data analysis was conducted through identification, classification, reduction, and exposition. The findings revealed varied themes: social criticism (35.5%), absurdism (17.7%), religion (13.3%), romanticism (4.4%), feminism (2.2%), and other themes (26.6%). Social criticism was the most dominant theme, followed by absurdism, religion, romanticism, feminism, and others. These works not only reflect emotional expression but also serve as a medium for critiquing discrimination and injustice experienced in society. The trauma expressed is primarily relational, such as social rejection and bullying, beyond just physical limitations. This study confirms that literary works are a vital means for individuals with disabilities to authentically voice their experiences and symbolically resist non-inclusive social systems. These findings aim to enrich interdisciplinary studies in literature, psychology, therapy, and disability studies.